O ausente-presente: Merleau-Ponty e o inconsciente primordial - Dors, Litiara Kohl (2020)
Merleau-Ponty, within the scope of his inaugural work, programmatically phenomenological, proposes a distance both in relation to empiricism and idealism. Most of all, it is a matter of describing the inseparableness between consciousness and the body, showing that the latter performs a kind of reflection. Reflection ceases to be a prerogative of pure and simple consciousness in order to radiate intentionally in bodily experience. There is an operative intentionality that spreads bodily. At the same time, in addition to the Husserlian phenomenological idealism, Merleau-Ponty also approaches Psychoanalysis and its corollary concept of the unconscious in order to resignify a certain ambiguous character that is part of the movement of corporeality and temporality. From the 1950s onwards, most notably in the Courses on Nature and Passivity, Merleau-Ponty returns, for example, to Freud in order to redefine, in a new key, the unconscious in its primordiality. This is due to the notion of primordial nature as a background or original horizon. From that moment until his last writings, in an increasingly recurrent approach to Psychoanalysis, Merleau-Ponty recognizes in the notion of the unconscious, a support point for the development of a new ontology, formulated by him in terms of an “ontological rehabilitation of the sensitive” with the most radical and forceful conceptual vector in the notion of flesh. Therefore, when developing an ontological perspective about the unconscious, the philosopher resorts, in turn, to the Kantian notion of negative greatness that sees a kind of real and non-logical opposition between a present and absent sense that is inscribed in the very dynamics of the unconscious. There is, say, a secret counterpart inherent in this double meaning as ontological dubbing. The unconscious opens up, therefore, as a primordial field revealing an absent-present aspect as a structure or layer. Well then, the primordial unconscious is this absent-present inherent in consciousness itself, which is no longer translucent or ideally purified, but ambiguous, carnal, permeated by gaps. It is in this perspective, more particularly, that Merleau-Ponty, in his late work, alludes, even in a fragmented way, to the idea of an “ontological psychoanalysis” in direct opposition to the Sartrian notion of “existential psychoanalysis”. Merleau-Ponty understands that perception leads to the appearance of a configuration between figure and background that is established between the living body and the elements of the perceived world. Everything happens as if the body operates a kind of mimicry with the world as flesh, in which it is no longer possible to purify what is part of one or the other. From this point of view, everything that appears appears against a background of ambiguous and non-thematic imperception, in which the unconscious itself emerges as a sui generis mode of absent / present structure. This new approach to perception also has an impact on the understanding of clinical cases, especially neurological and psychiatric ones, which Merleau-Ponty, to a large extent, supports by resorting to either clinical studies by Freud or even by Binswanger.